It'll Be Okay, Because We Belong Together: The Influence of Person-Organization Fit on Interpretation of Bad-News Messages in Academic Settings. Issue 5 (20th October 2018) - Frost, Jonathon K.; Edwards, Renee
Abstract : Higher education has recently faced significant budget cuts. In response, academic leaders must communicate negative information to stakeholders while simultaneously attempting to maintain morale and credibility. This project investigated how students interpret a bad-news message from the university president and examined the impact of person-organization fit and demographic characteristics on interpretations and credibility. In Study 1, participants (N = 52) provided 19 varying interpretations for a real-life message. Using 5 components derived from the interpretations, Study 2 (N = 466) determined that person-organization fit and demographic characteristics influence interpretations and source credibility. Some outcomes varied according to whether participants had previously read the bad-news message.